Antimicrobial Mechanism of Antimicrobial Peptide LL-1 against Salmonella - WANG Yuhang, ZHOU Lingling, ZHOU Yaoling, SA Junmeng, ZHANG Yuanchen, MA Zengjun, LIAN Kaiqi (Shipin Kexue)
To explore the antibacterial effect and mechanism of antimicrobial peptide LL-1 against Salmonella, the minimum inhibitory concentration (MIC) was determined by the doubling dilution method, and the antibacterial effect was evaluated by the growth inhibition curve. Then, the bacterial morphology was observed using scanning electron microscopy (SEM) and transmission electron microscopy (TEM). The effect of LL-1 on the cell wall and cell membrane of Salmonella was evaluated by detecting the leakage of intracellular nucleic acids, proteins and alkaline phosphatase (ALP) as well as by conducting propidium iodide (PI) staining experiments. The binding of LL-1 to Salmonella DNA was detected by nucleic acid gel electrophoresis. Finally, the effect of LL-1 on the energy metabolism of Salmonella was evaluated by measuring the activities of intracellular succinate dehydrogenase (SDH), NADP-malate dehydrogenase (NADP-MDH) and ATP levels. The results showed that the MIC was 6.25 μg/mL, and LL-1 had a good antibacterial effect in dose- and time-dependent manners. Salmonella treated with LL-1 showed morphological changes such as cell shrinkage, cell membrane dissolution, and plasmolysis. LL-1 resulted in the leakage of intracellular nucleic acids, proteins and ALP and an increase in the fluorescence intensity of PI-stained bacterial cells. Additionally, LL-1 could bind to bacterial DNA. Increasing LL-1 concentration resulted in a decrease in the intracellular ATP content, SDH and NADP-MDH activities. In conclusion, LL-1 could exert its antibacterial activity against Salmonella by increasing the permeability of the cell membrane and cell wall, thereby causing the leakage of intracellular contents, binding to DNA, and affecting bacterial energy metabolism. This study lays the foundation for further research on the antibacterial mechanism and application of LL-1.